Energy intensity: A decomposition and counterfactual exercise for Latin American countries - Raúl Jiménez; Jorge Mercado (Inter-American Development Bank (IDB), 2013)
This paper investigates trends in energy intensity in Latin American countries over the last 40 years. It applies the Fisher Ideal Index to decompose the energy intensity into the relative contributions of energy efficiency and the activity mix, and then analyzes the determinants of these energy indexes through panel data regression techniques. Finally, the paper compares the performance of Latin American countries to that of a similar set of countries chosen through the synthetic control method. The authors find that the energy intensity in Latin American countries has decreased about 20 percent, closing the gap with respect to its synthetic counterfactual. In both Latin American countries and its synthetic control, efficiency improvements drive these changes, while the activity mix component does not represent a clear source of change. The regression analysis shows that per capita income, petroleum prices, fuel-energy mix, and GDP growth are main determinants of energy intensity and efficiency, while there are no clear correlations with the activity component.
hdl:11319/4594
Keywords: O5; O13; Q40; Q43; 330; energy intensity; decomposition; panel data; synthetic control method